Development of Innovative Chemistry Teaching Materials for Molecular Geometry Using Recycled Materials - Marfu’ah, Siti; Asmawati, Rohana; Risha, Velina G.; Asra, Selli; Hotima, Husnul; Ristika, Dena; Izzah, Alifah D. (Proceeding International Conference on Religion, Science and Education, 2025)
The limitations of molecular geometry learning media in Indonesia often pose challenges in understanding abstract chemistry concepts, while commercial molecular models are relatively expensive for most educational institutions. This study aims to develop a prototype molecular model using recycled materials as an economical and sustainable alternative learning medium. An exploratory approach was employed in the prototype development, involving six students and one chemistry education lecturer. The materials used included plastic pipettes, marbles, skewers, bottle caps, and used cardboard, which were processed through a series of systematic stages. The research resulted in two distinct prototypes: the "Alkane Series" Model, showcasing a series of hydrocarbons from methane to propane (CH4, C2H6, C3H8), and the "Molecule Shape" Model, visualizing various geometric shapes of inorganic compound molecules (SO2, CO2, H2O, BF3, NH3, CH4). Durability evaluations indicated that both models exhibited good resilience after more than 50 repeated uses, while safety testing confirmed their compliance with usage standards in educational settings. The "Alkane Series" Model effectively visualized the pattern of atom addition in the alkane homologous series, while the "Molecule Shape" Model successfully demonstrated the variations in molecular geometry shapes, ranging from linear to tetrahedral. The use of recycled materials not only provides an economical solution to the limitations of learning media but also supports the implementation of education for sustainable development. Although standardization for large-scale production still requires further research, the findings of this study open opportunities for the development of recycled material-based learning media for other chemistry concepts.